Life-threatening complications after high-dose methotrexate and the benefits of glucarpidase as salvage therapy: a cohort study of 468 patients. Issue 4 (21st March 2021) - Medrano, Chloé; Oberic, Lucie; Puisset, Florent; Recher, Christian; Larrieu-Ciron, Delphine; Ysebaert, Loïc; Protin, Caroline; Picard, Muriel; Perriat, Sophie; Chatelut, Etienne; Bertoli, Sarah; Huguet, Françoise; et al.
Abstract: The aims of this study were to characterize the incidence and outcomes of severe toxicities following the administration of high-dose methotrexate (HD-MTX; ≥1 g/m 2 ). Among the 468 patients included in the study, 69 (14.9%) developed at least one episode of acute kidney injury (AKI; 138/1264 HD-MTX administrations), including 34 (7.2%) who developed KDIGO stage 2-3 AKI. The three baseline factors independently associated with the risk of developing AKI were age, body mass index and a diagnosis of acute lymphoblastic leukemia. Higher plasma MTX concentration was associated with AKI and extra-renal toxicities. Notwithstanding potentially confounding factors, most patients with AKI who received glucarpidase ( n  = 41) developed extra-renal toxicity (leading to the death of two patients) despite early administration. Thus, severe toxicity and death can occur whether or not glucarpidase is administered, which confirms the need for further interventional studies to provide greater precision on its role in the management of HD-MTX toxicity.